The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1177/1687814015618905
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility analysis of phase transition signals based on e-bike rider behavior

Abstract: This article evaluates the feasibility of two scenarios of phase transition signals, that is, the flashing green together with red-yellow light and the green countdown together with red countdown, at signalized intersections in terms of e-bike rider behavior. An evaluation framework is first proposed. During the phase transition, the stop-go and start-up behavioral parameters are collected at four intersections in Shanghai, China. Sensitivity analysis is then performed to identify the most significant factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…These studies are consistent in showing that flashing green reduces red-light violations that may result in right-angle collisions but increases conflicts during approach that may result in rear-end collisions that call for immediate action rather than preparatory warnings. In addition, Tang et al [26] and Dong et al [27,28] studied the impact of flashing green on e-bike driving behavior and found that potential time is the dominant independent factor explaining the stop/pass decision of e-bike drivers. In these cases, flashing green seemed to enlarge the option zone, bringing the indecision zone earlier and resulting in more aggressive driving behavior with regard to passing through intersections.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These studies are consistent in showing that flashing green reduces red-light violations that may result in right-angle collisions but increases conflicts during approach that may result in rear-end collisions that call for immediate action rather than preparatory warnings. In addition, Tang et al [26] and Dong et al [27,28] studied the impact of flashing green on e-bike driving behavior and found that potential time is the dominant independent factor explaining the stop/pass decision of e-bike drivers. In these cases, flashing green seemed to enlarge the option zone, bringing the indecision zone earlier and resulting in more aggressive driving behavior with regard to passing through intersections.…”
Section: Literature Reviewmentioning
confidence: 99%
“…ere are both positive and negative conclusions about the effect of FG in these kinds of literature studies. e positive results show that FG can warn the driver that the phase of green light is coming to an end, and the driver can reduce the incidence of DZ by reducing the driving speed, to avoid red light violations [1,2,9]. FG signal essentially plays a role in prolonging the duration of yellow light.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At signalized intersections in most cities of China, a 3 s green flashlight (FG) indicator and a 3 s yellow light (Y) indicator are the most common form of transition signal setting [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Oh and Kim [28] analysed the detailed vehicular movement and trajectories at intersections from traffic surveillance systems and estimated the crash potential with a probabilistic measurement. Dong et al [8] extracted the overall trajectories and investigated the distribution of the encroachment time and position to find significant factors influencing the interactions between cars and electric bikes. The above-mentioned methods try to define the potential conflict zone as a box of joint trajectories and describe the severity with the frequency numbers and distributions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…1). Shockingly, it is shown that more than half of the accidents at intersections are related to electric bikes in China [8], let alone the cyclists are much more vulnerable than the drivers in cars [9]. However, despite the plentiful experiments and analyses carried out for car flow and pedestrians [10][11][12][13][14], less attention is paid to electric bikes in the analysis of interactions and potential risks.…”
Section: Introductionmentioning
confidence: 99%